1997
DOI: 10.1136/bjo.81.9.789
|View full text |Cite
|
Sign up to set email alerts
|

Local hypothermia protects the retina from ischaemic injury in vitrectomy

Abstract: Aims-Hypothermic irrigating solutions were used during vitrectomy in pressure induced ischaemic eyes so that their eVects on retinal function and histological changes could be investigated. Methods-After anaesthetised albino rabbits underwent closed vitrectomy, their vitreous cavities were continuously irrigated for 30 minutes at a perfusion pressure of 140 mm Hg. The rabbits were divided into three groups according to their intraocular perfusion temperatures-8°C, 22°C, and 38°C. Electroretinograms were taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 17 publications
1
28
1
Order By: Relevance
“…We demonstrated in a previous paper that local hypothermia protected the retina from ischemic injury in vitrectomy (18). The reduction in the choroidal blood flow under local hypothermia may also be helpful in vitreoretinal surgery to decrease the incidence of massive choroidal hemorrhage and subsequent retinal damage.…”
Section: Discussionmentioning
confidence: 95%
“…We demonstrated in a previous paper that local hypothermia protected the retina from ischemic injury in vitrectomy (18). The reduction in the choroidal blood flow under local hypothermia may also be helpful in vitreoretinal surgery to decrease the incidence of massive choroidal hemorrhage and subsequent retinal damage.…”
Section: Discussionmentioning
confidence: 95%
“…Additional effects of local eye cooling are a decrease in intraocular and intravitreal pressure [20]. Local eye hypothermia has also been applied in cataract and refractive surgery [15,18,21]. Experimental studies have concluded, moreover, that hypothermia is well tolerated without any retinal damage at the level of 22 8C [22].…”
Section: Discussionmentioning
confidence: 99%
“…15 A balanced salt irrigation solution cooled to 7°C during vitrectomy results in less intraocular bleeding, fi brin production, or postoperative infl ammation, and there is no tissue intolerance to hypothermia. 16 Experimental intraocular moderate hypothermia is well tolerated, and leads to less infl ammation and damage [17][18][19] and good corneal results during photorefractive keratectomy. 20,21 …”
Section: Discussionmentioning
confidence: 99%